Can Music Make You Sick? Measuring the Price of Musical Ambition - Gross, Sally Anne (University of Westminster Press, 2020)
"Musicians often pay a high price for sharing their art with us. Underneath the glow of success can often lie loneliness and exhaustion, not to mention the basic struggles of paying the rent or buying food. Sally Anne Gross and George Musgrave raise important questions - and we need to listen to what the musicians have to tell us about their working conditions and their mental health." Emma Warren (Music Journalist and Author). "Singing is crying for grown-ups. To create great songs or play them with meaning music's creators reach far into emotion and fragility seeking the communion we demand of it. However, music's toll on musicians can leave deep scars. In this important book, Sally Anne Gross and George Musgrave investigate the relationship between the wellbeing music brings to society and the wellbeing of those who create. It's a much needed reality check, deglamorising the romantic image of the tortured artist." Crispin Hunt (Multi-Platinum Songwriter/Record Producer, Chair of the Ivors Academy). It is often assumed that creative people are prone to psychological instability, and that this explains apparent associations between cultural production and mental health problems. In their detailed study of recording and performing artists in the British music industry, Sally Anne Gross and George Musgrave turn this view on its head. By listening to how musicians understand and experience their working lives, this book proposes that whilst making music is therapeutic, making a career from music can be traumatic. The authors show how careers based on an all-consuming passion have become more insecure and devalued. Artistic merit and intimate, often painful, self-disclosures are the subject of unremitting scrutiny and data metrics. Personal relationships and social support networks are increasingly bound up with calculative transactions. Drawing on original empirical research and a wide-ranging survey of scholarship from across the social sciences, their findings will be provocative for future research on mental health, wellbeing and working conditions in the music industries and across the creative economy. Going beyond self-help strategies, they challenge the industry to make transformative structural change. Until then, the book provides an invaluable guide for anyone currently making their career in music, as well as those tasked with training and educating the next generation